2019
DOI: 10.14814/phy2.14063
|View full text |Cite
|
Sign up to set email alerts
|

The effect of IPC on central and peripheral fatiguing mechanisms in humans following maximal single limb isokinetic exercise

Abstract: Ischemic preconditioning ( IPC ) has been suggested to preserve neural drive during fatiguing dynamic exercise, however, it remains unclear as to whether this may be the consequence of IPC ‐enhanced muscle oxygenation. We hypothesized that the IPC ‐enhanced muscle oxygenation during a dynamic exercise task would subsequently attenuate exercise‐induced reductions in voluntary activation. Ten resistance trained males completed three 3 min maxim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
18
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 55 publications
(83 reference statements)
4
18
1
Order By: Relevance
“…Modulation of central mechanisms associated with fatigability such as voluntary activation and presynaptic inhibition [ 14 , 50 ] were not altered by IPC in the current study. This is in accordance with others who showed no effects of a single session of IPC on voluntary activation or H-reflex amplitude of the quadriceps muscles in men, but its effects in women were not evaluated [ 11 , 12 , 51 , 52 ]. Nonetheless, it is suggested that some individuals seem to respond to the IPC technique but others do not [ 10 , 52 , 53 ] and differences in the populations involved, the intensity of contraction and muscles recruited are some factors that may explain the contradictory findings across studies.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Modulation of central mechanisms associated with fatigability such as voluntary activation and presynaptic inhibition [ 14 , 50 ] were not altered by IPC in the current study. This is in accordance with others who showed no effects of a single session of IPC on voluntary activation or H-reflex amplitude of the quadriceps muscles in men, but its effects in women were not evaluated [ 11 , 12 , 51 , 52 ]. Nonetheless, it is suggested that some individuals seem to respond to the IPC technique but others do not [ 10 , 52 , 53 ] and differences in the populations involved, the intensity of contraction and muscles recruited are some factors that may explain the contradictory findings across studies.…”
Section: Discussionsupporting
confidence: 91%
“…There was no sex difference in physical activity levels in the current study, and therefore this variable likely does not explain the sex difference in response to IPC in our sample. The current study agrees with others that investigated the effects of IPC during fatiguing tasks at submaximal intensities using different muscle groups [ 6 , 52 ], but it is in contrast with others employing a maximal intensity task (e.g., all out sprint) in men [ 11 , 12 , 51 ] and women [ 55 ], and suggests the effects of IPC may be task dependent.…”
Section: Discussionsupporting
confidence: 91%
“…However, our data on central and peripheral determinants of performance fatigability as well as muscle activity, SmO 2 , and perceptual responses during exercise do not support this conclusion. Our results are in accordance with the outcomes of other studies that have neither found an increased exercise performance nor altered physiological and perceptual responses during and after submaximal and maximal exercise following IPC (Tocco et al, 2015;Sabino-Carvalho et al, 2017;Halley et al, 2018Halley et al, , 2019. Explanations for the discrepant outcomes of our study and that of Tanaka et al (2016) might be that they have not performed a warm-up after the interventions (IPC and the control condition) and before the fatigue protocol.…”
Section: Discussionsupporting
confidence: 89%
“…Recently, Halley et al (2018Halley et al ( , 2019 have found that IPC does not alter central and peripheral determinants of performance fatigability after maximal voluntary isometric and isokinetic exercise of the knee extensors compared to a sham treatment (SHAM). However, maximal voluntary contractions (MVC) induce complete or near-complete ischemia (Oranchuk et al, 2019), which renders modulations of blood flow due to IPC unlikely.…”
Section: Introductionmentioning
confidence: 99%
“…However, whereas sEMG can provide an estimate of gross nervous system output, a multitude of unrelated factors contribute to the sEMG signal (18,20,21). In an attempt to address these limitations, we incorporated the interpolated twitch technique into two separate studies (24,25); however, we failed to observe any influence of IPC on sEMG amplitudes, voluntary activation, or any other additional central or peripheral measures of neural drive.…”
Section: Introductionmentioning
confidence: 97%